High-strength aluminum alloy material and preparation method thereof
Aluminum alloy powder is prepared by water atomization method and mixed with specific additives. Combined with SLM technology and heat treatment, the problem of insufficient strength of 3D printed aluminum alloy materials is solved, and the preparation of high-strength aluminum alloy materials is realized to meet the high-end quality needs in aerospace and other fields.
Patent Information
- Application Number
- CN202510163673.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-02-14
AI Technical Summary
It is difficult for the prior art to obtain high-strength aluminum alloy materials that meet the high-end quality needs of aerospace and other fields through 3D printing. The materials are prone to cracking, warping, deformation and other problems during the printing process, resulting in insufficient strength.
Aluminum alloy powder was prepared by water atomization method, and mixed it with ditungsten boronide, vanadium diboride and polyacrylonitrile. After 3D printing through an SLM metal printer, heat treatment was performed to optimize the microstructure of the material and improve strength.
The aluminum alloy material obtained through this method has high tensile strength, yield strength and elongation after break, meeting the high-end quality needs in the fields of aerospace and other fields.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum alloy preparation, and particularly relates to a high-strength aluminum alloy material and a preparation method thereof. Background Art
[0002] 3D printing technology, also known as Additive Manufacturing (AM), is based on the following principles: using digital model files as instructions, digital technology material printers as equipment, and metal or plastic adhesive powders as materials, to quickly construct parts and products by printing layer by layer. 3D printing is a process of stacking materials layer by layer to create objects, rather than the traditional subtractive manufacturing method. 3D printing does not require original blanks and molds, and the design is more flexible.
[0003] The most mature 3D printing method at present is the laser selective melting technology, namely SLM technology. Its working method is: using a precisely focused laser spot to quickly melt the pre-laid layers of metal powder, you can directly obtain parts of any shape. Steel, titanium alloy, and aluminum alloy are relatively common metal bondable powders. Among them, aluminum alloy has the advantages of low density, high specific strength, good toughness and corrosion resistance. It is an indispensable important structural material in the aerospace, transportation, and machinery manufacturing industries. Therefore, obtaining high-strength aluminum alloy materials through 3D printing has broad application prospects.
[0004] Compared with other metal materials such as stainless steel and titanium alloy, aluminum alloy has advantages such as high thermal conductivity and good forming performance. However, aluminum alloy has high reflectivity to laser, low absorption rate to laser, easy oxidation and high thermal conductivity. It often cracks, warps, deforms, and spheroidizes during 3D printing. Printed components have problems such as low density, brittleness, warping, and cracking. It is one of the most difficult materials to print in 3D printing technology. The final product is often not strong enough to meet the high-end quality requirements of aerospace and other fields. Therefore, it is of great significance to develop aluminum alloy materials suitable for 3D printing technology.
[0005] Patent CN110423923B discloses an aluminum alloy suitable for 3D printing. Compared with AlSi10Mg alloy, the increase in the Mg content in the alloy of the present invention and the introduction of trace Sc and Zr elements have improved the yield strength of the patented alloy. The Si content in the patented alloy is not far from the eutectic composition, has good process characteristics in the 3D printing process, and has a low tendency to crack during the printing process. Compared with the AlSi10Mg alloy, the patented alloy introduces trace amounts of Sc and Zr elements, which can significantly improve the anisotropy of the alloy. However, the tensile strength of the aluminum alloy material obtained by 3D printing recorded in the patent is lower than 500MPa, the yield strength is lower than 300MPa, and the elongation after fracture is not higher than 8.0%, which still cannot meet the high-end quality requirements in fields such as aerospace. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high-strength aluminum alloy material and a preparation method thereof, which is obtained through 3D printing technology and has high strength to meet the high-end quality requirements in the fields of aerospace and the like.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] A method for preparing a high-strength aluminum alloy material comprises the following steps of preparing aluminum alloy powder by water atomization: Cu 4.1-4.5%, Mg 2.8-3.1%, Cr 2.5-2.8%, Si 1.2-1.5%, Mn 1.0-1.2%, Sc 0.3-0.5%, Zr 0.1-0.2%, Mo 0.08-0.1%, Ce 0.05-0.07%, Yb 0.05-0.07%, and the balance being Al; and then mixing the aluminum alloy powder with BW 2 (tungsten diboride), VB 2 (vanadium diboride) and polyacrylonitrile are mixed to obtain a mixed powder, which is 3D printed using an SLM metal printer and subjected to heat treatment to obtain an aluminum alloy material.
[0009] Preferably, the aluminum alloy powder is prepared by the following method: mixing the components in the formula and heating to 1000-1100° C., keeping the temperature for 50-60 minutes to obtain a molten liquid; atomizing the molten liquid with water, and drying to obtain the aluminum alloy powder.
[0010] More preferably, citric acid-sodium citrate buffer solution is used for water atomization, and the water atomization conditions are as follows: the melt flow diameter is 25-30 mm, the temperature of the citric acid-sodium citrate buffer solution is 30-40° C., the pressure is 90-100 MPa, and the flow rate is 180-190 m 3 / h, spray angle 20~23°.
[0011] More preferably, the concentration of citric acid-sodium citrate buffer is 0.1 mol / L, and pH=4.4.
[0012] Preferably, aluminum alloy powder, BW 2 ,VB 2 , and polyacrylonitrile are in a mass ratio of 1:0.1~0.2:0.1~0.2:0.1~0.2.
[0013] Preferably, BW 2 ,VB 2 The particle size is 1500-2000 mesh.
[0014] Preferably, the mixed powder is prepared by the following method: firstly, ultrasonically dispersing aluminum alloy powder in an aqueous solution of sodium dodecylbenzene sulfonate to obtain an aluminum alloy dispersion; then 2 ,VB 2 Ultrasonic dispersion is performed in deionized water to obtain a suspension; then the suspension and polyacrylonitrile solution are added to the aluminum alloy dispersion, fully stirred, filtered to obtain the solid, and dried to obtain the product.
[0015] Further preferably, the dosage ratio of the aluminum alloy powder to the sodium dodecylbenzene sulfonate aqueous solution is 1 g: 3-4 mL, and the mass concentration of the sodium dodecylbenzene sulfonate aqueous solution is 1-2%; BW 2 ,VB 2 , the dosage ratio of deionized water is 0.1-0.2g:0.1-0.2g:0.4-0.5mL; the dosage of polyacrylonitrile solution is 1 / 3-1 / 2 of the volume of the aluminum alloy dispersion, and the polyacrylonitrile solution is obtained by dissolving polyacrylonitrile in 5-6 times its weight of dimethyl sulfoxide.
[0016] More preferably, the process conditions for sufficient stirring are: stirring at 400-500 r / min for 3-4 hours.
[0017] Preferably, the specific parameters for 3D printing using an SLM metal printer are as follows: laser power 300-350 W, laser scanning rate 800-900 mm / s, laser scanning spacing 80-90 μm, the thickness of each layer of mixed powder molding is 30-40 μm, and the inter-layer rotation angle is 60-62°.
[0018] Preferably, the substrate of the SLM metal printer is preheated to 150-160° C. before use.
[0019] Preferably, the specific process of heat treatment is as follows:
[0020] (a) heating to 170-180°C at 8-10°C / min and keeping at this temperature for 2-3 hours;
[0021] (b) cooling to -30 to -40°C at a rate of 15 to 18°C / min and keeping warm for 3 to 4 hours;
[0022] (c) Transfer to a spark plasma sintering furnace for heat preservation, with a pulse current density of 250-280 A / cm 2 , the temperature is 180-200°C, the heating rate is 45-50°C / min, and the holding time is 40-50 minutes;
[0023] (d) heating to 280-300°C at a rate of 25-30°C / min and keeping the temperature for 1-2 hours;
[0024] (e) Cool naturally to room temperature.
[0025] A high-strength aluminum alloy material is obtained by the above-mentioned preparation method.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention first prepares aluminum alloy powder by water atomization method using Cu, Mg, Cr, Si, Mn, Sc, Zr, Mo, Ce, Yb, Al and the like in specific proportions; then the aluminum alloy powder is mixed with BW 2 (tungsten diboride), VB 2 (vanadium diboride) and polyacrylonitrile are mixed to obtain a mixed powder, which is 3D printed by an SLM metal printer and heat treated to obtain a high-strength aluminum alloy material. The aluminum alloy material of the present invention is obtained by 3D printing technology, has high strength, and meets the high-end quality requirements of aerospace and other fields.
[0028] The applicant screened and adjusted the composition of the aluminum alloy powder to ensure the basic strength requirements of the aluminum alloy material. The aluminum alloy powder is prepared by water atomization and is suitable for use in SLM technology.
[0029] The present invention further introduces ditungsten boride and vanadium diboride to further improve the strength of the aluminum alloy. Polyacrylonitrile is fiberized to form carbon fibers during subsequent treatment, which helps to further improve the strength of the aluminum alloy.
[0030] Heat treatment after 3D printing with an SLM metal printer, including heating, cooling, and reheating, helps optimize the microstructure of aluminum alloy materials and improve the strength of aluminum alloys. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Unless otherwise specified, all commodities in this invention are purchased through market channels.
[0033] The polyacrylonitrile in the examples and comparative examples has a weight average molecular weight of 100,000 and is purchased from Shenzhen Dansheng Plastic Co., Ltd.
[0034] Example 1
[0035] A method for preparing a high-strength aluminum alloy material, the specific steps are as follows:
[0036] S1. First, aluminum alloy powder is prepared by water atomization method by the following components in mass percentage: Cu 4.1%, Mg 2.8%, Cr 2.5%, Si 1.2%, Mn 1.0%, Sc 0.3%, Zr 0.1%, Mo 0.08%, Ce 0.05%, Yb 0.05%, and the balance is Al;
[0037] Specifically, the components of the formula are mixed and heated to 1000° C., and kept warm for 50 minutes to obtain a molten solution; the molten solution is atomized with citric acid-sodium citrate buffer (0.1 mol / L, pH=4.4) and dried to obtain the aluminum alloy powder;
[0038] The water atomization conditions are as follows: the melt flow diameter is 25 mm, the temperature of the citric acid-sodium citrate buffer is 30 °C, the pressure is 90 MPa, and the flow rate is 180 m 3 / h, spray angle 20°;
[0039] S2. Then the aluminum alloy powder and BW 2 (tungsten diboride), VB 2 (vanadium diboride) and polyacrylonitrile are mixed to obtain a mixed powder;
[0040] Specifically, 1 kg of aluminum alloy powder was ultrasonically dispersed in 3 L of sodium dodecylbenzene sulfonate aqueous solution (mass concentration 1%) to obtain an aluminum alloy dispersion; then 0.1 kg of BW 2 、0.1kg VB 2Ultrasonic dispersion was performed in 0.4 L of deionized water to obtain a suspension; then the suspension and the polyacrylonitrile solution were added to the aluminum alloy dispersion, stirred thoroughly (stirring at 400 r / min for 3 hours), the solid was filtered out, and dried to obtain the product; the amount of the polyacrylonitrile solution was 1 / 3 of the volume of the aluminum alloy dispersion, and the polyacrylonitrile solution was obtained by dissolving 0.1 kg of polyacrylonitrile in 5 times its weight of dimethyl sulfoxide; BW 2 ,VB 2 The particle size is 1500 mesh;
[0041] S3. 3D printing using SLM metal printer;
[0042] The specific parameters are as follows: laser power 300W, laser scanning rate 800mm / s, laser scanning spacing 80μm, the thickness of each layer of mixed powder is 30μm, and the inter-layer rotation angle is 60°;
[0043] The substrate of the SLM metal printer is preheated to 150°C before use;
[0044] The printing atmosphere uses argon gas, and the printing size is 50mm×50mm×50mm;
[0045] S4. Heat treatment;
[0046] The specific process is as follows:
[0047] (a) Raise the temperature to 170°C at 8°C / min and keep at this temperature for 2 hours;
[0048] (b) cooling to -30°C at 15°C / min and keeping warm for 3 hours;
[0049] (c) Transfer to spark plasma sintering furnace for heat preservation, pulse current density is 250A / cm 2 , the temperature is 180℃, the heating rate is 45℃ / min, and the holding time is 40 minutes;
[0050] (d) heating to 280°C at 25°C / min and keeping at this temperature for 1 hour;
[0051] (e) Cool naturally to room temperature.
[0052] Example 2
[0053] A method for preparing a high-strength aluminum alloy material, the specific steps are as follows:
[0054] S1. First, aluminum alloy powder is prepared by water atomization method by the following components in mass percentage: Cu 4.5%, Mg 3.1%, Cr 2.8%, Si 1.5%, Mn 1.2%, Sc 0.5%, Zr 0.2%, Mo 0.1%, Ce 0.07%, Yb 0.07%, and the balance is Al;
[0055] Specifically, the components of the formula are mixed and heated to 1100° C., and kept warm for 60 minutes to obtain a molten solution; the molten solution is atomized with citric acid-sodium citrate buffer (0.1 mol / L, pH=4.4) and dried to obtain the aluminum alloy powder;
[0056] The water atomization conditions are as follows: the melt flow diameter is 30 mm, the temperature of the citric acid-sodium citrate buffer is 40 °C, the pressure is 100 MPa, and the flow rate is 190 m 3 / h, spray angle 23°;
[0057] S2. Then the aluminum alloy powder and BW 2 (tungsten diboride), VB 2 (vanadium diboride) and polyacrylonitrile are mixed to obtain a mixed powder;
[0058] Specifically, 1 kg of aluminum alloy powder was ultrasonically dispersed in 4 L of sodium dodecylbenzene sulfonate aqueous solution (mass concentration 2%) to obtain an aluminum alloy dispersion; then 0.2 kg of BW 2 、0.2kg VB 2 Ultrasonic dispersion was performed in 0.5L deionized water to obtain a suspension; then the suspension and polyacrylonitrile solution were added to the aluminum alloy dispersion, stirred thoroughly (stirring at 500r / min for 4 hours), the solid was filtered out, and dried to obtain the product; the amount of polyacrylonitrile solution used was 1 / 2 of the volume of the aluminum alloy dispersion, and the polyacrylonitrile solution was obtained by dissolving 0.2kg of polyacrylonitrile in 6 times its weight of dimethyl sulfoxide; BW 2 ,VB 2 The particle size is 2000 mesh;
[0059] S3. 3D printing using SLM metal printer;
[0060] The specific parameters are as follows: laser power 350W, laser scanning rate 900mm / s, laser scanning spacing 90μm, the thickness of each layer of mixed powder is 40μm, and the inter-layer rotation angle is 62°;
[0061] The substrate of the SLM metal printer is preheated to 160°C before use;
[0062] The printing atmosphere uses argon gas, and the printing size is 50mm×50mm×50mm;
[0063] S4. Heat treatment;
[0064] The specific process is as follows:
[0065] (a) Raise the temperature to 180°C at 10°C / min and keep at this temperature for 3 hours;
[0066] (b) cooling to -40°C at 18°C / min and keeping warm for 4 hours;
[0067] (c) Transferred to a spark plasma sintering furnace for heat preservation, with a pulse current density of 280 A / cm 2 , temperature is 200℃, heating rate is 50℃ / min, holding time is 50 minutes;
[0068] (d) heating to 300°C at 30°C / min and keeping at this temperature for 2 hours;
[0069] (e) Cool naturally to room temperature.
[0070] Example 3
[0071] A method for preparing a high-strength aluminum alloy material, the specific steps are as follows:
[0072] S1. First, aluminum alloy powder is prepared by water atomization method by using the following components in mass percentage: Cu 4.3%, Mg3%, Cr2.7%, Si 1.3%, Mn 1.1%, Sc 0.4%, Zr 0.15%, Mo 0.09%, Ce 0.06%, Yb0.06%, and the balance is Al;
[0073] Specifically, the components of the formula are mixed and heated to 1050° C., and kept warm for 55 minutes to obtain a molten solution; the molten solution is atomized with citric acid-sodium citrate buffer (0.1 mol / L, pH=4.4) and dried to obtain the aluminum alloy powder;
[0074] The water atomization conditions are as follows: melt flow diameter is 28 mm, temperature of citric acid-sodium citrate buffer is 35 °C, pressure is 95 MPa, flow rate is 185 m 3 / h, spray angle 22°;
[0075] S2. Then the aluminum alloy powder and BW 2 (tungsten diboride), VB 2 (vanadium diboride) and polyacrylonitrile are mixed to obtain a mixed powder;
[0076] Specifically, 1 kg of aluminum alloy powder was ultrasonically dispersed in 3.5 L of sodium dodecylbenzene sulfonate aqueous solution (mass concentration 1.5%) to obtain an aluminum alloy dispersion; then 0.15 kg of BW 2 、0.15kg VB 2Ultrasonic dispersion was performed in 0.45 L of deionized water to obtain a suspension; then the suspension and the polyacrylonitrile solution were added to the aluminum alloy dispersion, stirred thoroughly (stirring at 500 r / min for 3 hours), the solid was filtered out, and dried to obtain the product; the amount of the polyacrylonitrile solution was 1 / 2 of the volume of the aluminum alloy dispersion, and the polyacrylonitrile solution was obtained by dissolving 0.15 kg of polyacrylonitrile in 5 times its weight of dimethyl sulfoxide; BW 2 ,VB 2 The particle size is 2000 mesh;
[0077] S3. 3D printing using SLM metal printer;
[0078] The specific parameters are as follows: laser power 330W, laser scanning rate 850mm / s, laser scanning spacing 85μm, the thickness of each layer of mixed powder is 35μm, and the inter-layer rotation angle is 61°;
[0079] The substrate of the SLM metal printer is preheated to 155°C before use;
[0080] The printing atmosphere uses argon gas, and the printing size is 50mm×50mm×50mm;
[0081] S4. Heat treatment;
[0082] The specific process is as follows:
[0083] (a) Raise the temperature to 175°C at 9°C / min and keep at this temperature for 2 hours;
[0084] (b) cooling to -35°C at 16°C / min and keeping warm for 3 hours;
[0085] (c) Transferred to a spark plasma sintering furnace for heat preservation, with a pulse current density of 260 A / cm 2 , the temperature is 190℃, the heating rate is 48℃ / min, and the holding time is 45 minutes;
[0086] (d) heating to 290°C at 28°C / min and keeping at this temperature for 1.5 hours;
[0087] (e) Cool naturally to room temperature.
[0088] Comparative Example 1
[0089] A method for preparing an aluminum alloy material, the specific steps are as follows:
[0090] S1. First, aluminum alloy powder is prepared by water atomization method by the following components in mass percentage: Cu 4.1%, Mg 2.8%, Cr 2.5%, Si 1.2%, Mn 1.0%, Sc 0.3%, Zr 0.1%, Mo 0.08%, Ce 0.05%, Yb 0.05%, and the balance is Al;
[0091] Specifically, the components of the formula are mixed and heated to 1000° C., and kept warm for 50 minutes to obtain a molten solution; the molten solution is atomized with citric acid-sodium citrate buffer (0.1 mol / L, pH=4.4) and dried to obtain the aluminum alloy powder;
[0092] The water atomization conditions are as follows: the melt flow diameter is 25 mm, the temperature of the citric acid-sodium citrate buffer is 30 °C, the pressure is 90 MPa, and the flow rate is 180 m 3 / h, spray angle 20°;
[0093] S2. Then the aluminum alloy powder and BW 2 (ditungsten boride) and polyacrylonitrile are mixed to obtain a mixed powder;
[0094] Specifically, 1 kg of aluminum alloy powder was ultrasonically dispersed in 3 L of sodium dodecylbenzene sulfonate aqueous solution (mass concentration 1%) to obtain an aluminum alloy dispersion; then 0.1 kg of BW 2 Ultrasonic dispersion was performed in 0.4 L of deionized water to obtain a suspension; then the suspension and the polyacrylonitrile solution were added to the aluminum alloy dispersion, stirred thoroughly (stirring at 400 r / min for 3 hours), the solid was filtered out, and dried to obtain the product; the amount of the polyacrylonitrile solution was 1 / 3 of the volume of the aluminum alloy dispersion, and the polyacrylonitrile solution was obtained by dissolving 0.1 kg of polyacrylonitrile in 5 times its weight of dimethyl sulfoxide; BW 2 The particle size is 1500 mesh;
[0095] S3. 3D printing using SLM metal printer;
[0096] The specific parameters are as follows: laser power 300W, laser scanning rate 800mm / s, laser scanning spacing 80μm, the thickness of each layer of mixed powder is 30μm, and the inter-layer rotation angle is 60°;
[0097] The substrate of the SLM metal printer is preheated to 150°C before use;
[0098] The printing atmosphere uses argon gas, and the printing size is 50mm×50mm×50mm;
[0099] S4. Heat treatment;
[0100] The specific process is as follows:
[0101] (a) Raise the temperature to 170°C at 8°C / min and keep at this temperature for 2 hours;
[0102] (b) cooling to -30°C at 15°C / min and keeping warm for 3 hours;
[0103] (c) Transfer to spark plasma sintering furnace for heat preservation, pulse current density is 250A / cm 2 , the temperature is 180℃, the heating rate is 45℃ / min, and the holding time is 40 minutes;
[0104] (d) heating to 280°C at 25°C / min and keeping at this temperature for 1 hour;
[0105] (e) Cool naturally to room temperature.
[0106] Comparative Example 2
[0107] A method for preparing an aluminum alloy material, the specific steps are as follows:
[0108] S1. First, aluminum alloy powder is prepared by water atomization method by the following components in mass percentage: Cu 4.1%, Mg 2.8%, Cr 2.5%, Si 1.2%, Mn 1.0%, Sc 0.3%, Zr 0.1%, Mo 0.08%, Ce 0.05%, Yb 0.05%, and the balance is Al;
[0109] Specifically, the components of the formula are mixed and heated to 1000° C., and kept warm for 50 minutes to obtain a molten solution; the molten solution is atomized with citric acid-sodium citrate buffer (0.1 mol / L, pH=4.4) and dried to obtain the aluminum alloy powder;
[0110] The water atomization conditions are as follows: the melt flow diameter is 25 mm, the temperature of the citric acid-sodium citrate buffer is 30 °C, the pressure is 90 MPa, and the flow rate is 180 m 3 / h, spray angle 20°;
[0111] S2. Then the aluminum alloy powder and BW 2 (tungsten diboride), VB 2 (vanadium diboride) to obtain a mixed powder;
[0112] Specifically, 1 kg of aluminum alloy powder was ultrasonically dispersed in 3 L of sodium dodecylbenzene sulfonate aqueous solution (mass concentration 1%) to obtain an aluminum alloy dispersion; then 0.1 kg of BW 2 、0.1kg VB 2 Ultrasonic dispersion was performed in 0.4 L of deionized water to obtain a suspension; the suspension was then added to the aluminum alloy dispersion, stirred thoroughly (400 r / min for 3 hours), the solid was filtered and dried to obtain BW. 2 ,VB 2 The particle size is 1500 mesh;
[0113] S3. 3D printing using SLM metal printer;
[0114] The specific parameters are as follows: laser power 300W, laser scanning rate 800mm / s, laser scanning spacing 80μm, the thickness of each layer of mixed powder is 30μm, and the inter-layer rotation angle is 60°;
[0115] The substrate of the SLM metal printer is preheated to 150°C before use;
[0116] The printing atmosphere uses argon gas, and the printing size is 50mm×50mm×50mm;
[0117] S4. Heat treatment;
[0118] The specific process is as follows:
[0119] (a) Raise the temperature to 170°C at 8°C / min and keep at this temperature for 2 hours;
[0120] (b) cooling to -30°C at 15°C / min and keeping warm for 3 hours;
[0121] (c) Transfer to spark plasma sintering furnace for heat preservation, pulse current density is 250A / cm 2 , the temperature is 180℃, the heating rate is 45℃ / min, and the holding time is 40 minutes;
[0122] (d) heating to 280°C at 25°C / min and keeping at this temperature for 1 hour;
[0123] (e) Cool naturally to room temperature.
[0124] The performance tests were conducted on the aluminum alloy materials obtained in Examples 1 to 3 and Comparative Examples 1 and 2, respectively. Specifically, the tensile strength, yield strength and elongation after fracture were tested on an electronic universal testing machine (model: AG-X 100kN). The results are shown in Table 1.
[0125] Table 1. Aluminum alloy performance test results
[0126] Tensile strength(MPa) Yield strength (MPa) Elongation after break (%) Example 1 593 568 12.2 Example 2 595 572 12.2 Example 3 598 576 12.1 Comparative Example 1 567 522 13.0 Comparative Example 2 553 509 13.0
[0127] It can be seen from Table 1 that the aluminum alloy materials obtained in Examples 1 to 3 have high tensile strength, yield strength, and elongation after fracture, and have excellent performance.
[0128] Comparative Example 1 omitted vanadium diboride, and Comparative Example 2 omitted polyacrylonitrile, and the strength was significantly reduced, indicating that BW 2 (tungsten diboride), VB 2 The addition of (vanadium diboride) and polyacrylonitrile is beneficial to improving the strength of aluminum alloy materials.
[0129] The present invention illustrates the technical concept of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of individual raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a high-strength aluminum alloy material, characterized in that: First, the following components in mass percentage are prepared by water atomization method: Cu 4.1-4.5%, Mg 2.8-3.1%, Cr 2.5-2.8%, Si 1.2-1.5%, Mn 1.0-1.2%, Sc 0.3-0.5%, Zr 0.1-0.2%, Mo 0.08-0.1%, Ce 0.05-0.07%, Yb 0.05-0.07%, and the balance is Al; then the aluminum alloy powder is mixed with BW2, VB2, and polyacrylonitrile to obtain a mixed powder, which is 3D printed using an SLM metal printer and heat treated to obtain an aluminum alloy material.
2. The preparation method according to claim 1, characterized in that: The aluminum alloy powder is prepared by the following method: mixing the components of the formula and heating to 1000-1100° C., keeping the temperature for 50-60 minutes to obtain a molten liquid; atomizing the molten liquid with water, and drying to obtain the aluminum alloy powder.
3. The preparation method according to claim 1, characterized in that: The mass ratio of aluminum alloy powder, BW2, VB2 and polyacrylonitrile is 1:0.1~0.2:0.1~0.2:0.1~0.
2.
4. The preparation method according to claim 1, characterized in that: The particle size of BW2 and VB2 is 1500-2000 mesh.
5. The preparation method according to claim 1, characterized in that: The mixed powder is prepared by the following method: firstly, ultrasonically dispersing aluminum alloy powder in a sodium dodecylbenzene sulfonate aqueous solution to obtain an aluminum alloy dispersion; then, ultrasonically dispersing BW2 and VB2 in deionized water to obtain a suspension; then, adding the suspension and polyacrylonitrile solution to the aluminum alloy dispersion, stirring sufficiently, filtering to obtain the solid, and drying to obtain the mixed powder.
6. The preparation method according to claim 1, characterized in that: The specific parameters of 3D printing using the SLM metal printer are as follows: laser power 300-350 W, laser scanning rate 800-900 mm / s, laser scanning spacing 80-90 μm, the thickness of each layer of mixed powder molding is 30-40 μm, and the inter-layer rotation angle is 60-62°.
7. The preparation method according to claim 1, characterized in that: The substrate of the SLM metal printer is preheated to 150-160°C before use.
8. The preparation method according to claim 1, characterized in that: The specific process of heat treatment is as follows: (a) heating to 170-180°C at 8-10°C / min and keeping at this temperature for 2-3 hours; (b) cooling to -30 to -40°C at a rate of 15 to 18°C / min and keeping warm for 3 to 4 hours; (c) Transfer to spark plasma sintering furnace for heat preservation, pulse current density is 250~280A / cm 2 , the temperature is 180-200°C, the heating rate is 45-50°C / min, and the holding time is 40-50 minutes; (d) heating to 280-300°C at a rate of 25-30°C / min and keeping the temperature for 1-2 hours; (e) Cool naturally to room temperature.
9. A high-strength aluminum alloy material, characterized in that: The invention is obtained by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
An aluminum alloy suitable for 3D printing
CN110423923B
Spacecraft structure material and nano aluminum alloy composite material thereof
CN103205609A
Composite material for 3D printing engine cylinder cover and preparation method thereof
CN105598441A
Aluminum alloy powder capable of being used for 3D printing and preparing method and application of aluminum alloy powder
CN109487126A
Aluminum alloy and machining method thereof
CN111197147A